Großer Schub oder kleiner Schubs? ‚Corona-Krise‘ als Initialzündung für digitalere Schule in Deutschland. - Eickelmann, Birgit

Zwischen Aufbruch und Krise. Narrative Auseinandersetzungen mit der spanischen Transición und der deutschen 'Wende'

Fortschrittskontrolle der Modellierung mechatronischer Produkte - Gräßler, Iris; Wiechel, Dominik; Thiele, Henrik (Tagungsband der Fachtagung VDI-Mechatronik)
Die Anforderungen an die Entwicklung mechatronischer Systeme sind seit der Erstfassung der VDI Richtlinie 2206 im Jahr 2004 stetig gestiegen. Nach einer umfassenden Überarbeitung ist 2021 die Richtline im Weißdruck neu veröffentlicht worden. Neben dem Systemdenken als gestärktes Kernelement des V-Modells und sechs Kontrollpunkten nur Gliederung der sachlogischen Aufgaben ist die durchgängig explizite „Modellierung und Analyse“ eine wesentliche Neuerung der Richtlinie. Da sich die Kontrollfragen nur auf den Entwicklungsprozess im Ganzen beziehen, wird durch die Betrachtung der Modellierung eines Batteriesystems aus einem Entwicklungsprojekt eines deutschen Automobilherstellers die folgende Forschungsfrage betrachtet: Welche spezifischen Kontrollfragen zu Fortschritt und Reifegrad der Modellierung eines Batteriesystems können aus den Kontrollpunkten des V-Modells (VDI 2206:2020) gefolgert werden? Als Ergebnis der Forschung liegen hinsichtlich der Modellierung eines spezifischen Systems detaillierte Kontrollfragen vor, die eine methodische Unterstützung für die modellbasierte Systementwicklung komplexer mechatronischer Systeme bieten. Zusätzlich ermöglichen sie der Projektleitung die Überprüfung des aktuellen Status der Entwicklung und sichern die Vollständigkeit des Systemmodells ab.

Approach to Sustainability-Based Assessment of Solution Alternatives in Early Stages of Product Engineering - Gräßler, Iris; Hesse, Philipp (Proceedings of the Design Society)
Sustainable product engineering is becoming increasingly important. This includes the development of environmentally friendly products and the design for recycling. In this paper a holistic method for the assessment of solution alternatives is presented, in which the stakeholder perspectives along the generic product lifecycle are taken into account. Finally, a new visualization is presented. By visualizing the results in the integrated sustainability triangle, decision-makers in product development can holistically assess the sustainability of the solution alternatives.
Keywords: sustainability; decision making; generic product lifecycle; design analysis; ecodesign

Model-Based Effect-Chain Analysis for Complex Systems - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Preuß, Daniel; Oleff, Christian (Proceedings of the Design Society)
Abstract Effect chain modeling approaches are applied to model cause-effect relations and analyze affected elements and dependencies. In this paper a systematic literature research is conducted to derive main characteristics and limitations of existing approaches. Then, the Model-based Effect Chain Analysis (MECA) method is introduced. Evaluation proves applicability of the method by means of a case example. This is done in the context of a project with a German automotive company. In the project 66 workshops were conducted to model certification-compliant effect chains in accordance to the UN ECE 156.

Untersuchung essenzieller Eigenschaften wasserlöslicher Polymere für die Anwendung zur Polymerpulverherstellung - Zhang, Xiandong; Neukötter, Moritz

Einsatz und Evaluation von Virtual Reality-Technologie in einem Informatik-Seminar - Yigitbas, Enes

Multichannel Superposition of Grafted Perfect Vortex Beams - Ahmed, Hammad; Intaravanne, Yuttana; Ming, Yang; Ansari, Muhammad Afnan; Buller, Gerald S.; Zentgraf, Thomas; Chen, Xianzhong (Advanced Materials)
Inspired by plant grafting, grafted vortex beams can be formed through grafting two or more helical phase profiles of optical vortex beams. Recently, grafted perfect vortex beams (GPVBs) have attracted much attention due to their unique optical properties and potential applications. However, the current method to generate and manipulate GPVBs requires a complex and bulky optical system, hindering further investigation and limiting its practical applications. Here, a compact metasurface approach for generating and manipulating GPVBs in multiple channels is proposed and demonstrated, which eliminates the need for such a complex optical setup. A single metasurface is utilized to realize various superpositions of GPVBs with different combinations of topological charges in four channels, leading to asymmetric singularity distributions. The positions of singularities in the superimposed beam can be further modulated by introducing an initial phase difference in the metasurface design. The work demonstrates a compact metasurface platform that performs a sophisticated optical task that is very challenging with conventional optics, opening opportunities for the investigation and applications of GPVBs in a wide range of emerging application areas, such as singular optics and quantum science.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Friendship: Communicative negotiation in proximity and distance - Teichert, Jeannine (Mediatisation of Emotional Life)

Symmetric Set Coloring of Signed Graphs - Cappello, Chiara; Steffen, Eckhard (Annals of Combinatorics)
There are many concepts of signed graph coloring which are defined by assigning colors to the vertices of the graphs. These concepts usually differ in the number of self-inverse colors used. We introduce a unifying concept for this kind of coloring by assigning elements from symmetric sets to the vertices of the signed graphs. In the first part of the paper, we study colorings with elements from symmetric sets where the number of self-inverse elements is fixed. We prove a Brooks’-type theorem and upper bounds for the corresponding chromatic numbers in terms of the chromatic number of the underlying graph. These results are used in the second part where we introduce the symset-chromatic number χsym(G,σ) of a signed graph (G,σ). We show that the symset-chromatic number gives the minimum partition of a signed graph into independent sets and non-bipartite antibalanced subgraphs. In particular, χsym(G,σ)≤χ(G). In the final section we show that these colorings can also be formalized as DP-colorings.
Keywords: Discrete Mathematics and Combinatorics

Even Factors in Edge-Chromatic-Critical Graphs with a Small Number of Divalent Vertices - Steffen, Eckhard; Wolf, Isaak Hieronymus (Graphs and Combinatorics)
Keywords: Discrete Mathematics and Combinatorics; Theoretical Computer Science

Frustration-critical signed graphs - Cappello, Chiara; Steffen, Eckhard (Discrete Applied Mathematics)
Keywords: Applied Mathematics; Discrete Mathematics and Combinatorics

Edge colorings and circular flows on regular graphs - Mattiolo, Davide; Steffen, Eckhard (Journal of Graph Theory)

Model-driven Design and Management of Professional Education Programmes - Wolters, Dennis; Engels, Gregor (ICSOB'22 Companion Proceedings)

Raman Optical Activity of N-Acetyl-L-Cysteine in Water and in Methanol: The “Clusters-in-a-Liquid” Model and ab initio Molecular Dynamics Simulations - Yang, Y.; Cheramy, J.; Brehm, Martin; Xu, Y. (ChemPhysChem)

Transferable Deep Learning Potential Reveals Intermediate-Range Ordering Effects in LiF–NaF–ZrF4 Molten Salt - Chahal, R.; Roy, S.; Brehm, Martin; Banerjee, S.; Bryantsev, V.; Lam, S. (JACS Au)

Conformer Weighting and Differently Sized Cluster Weighting for Nicotine and its Phosphorus Derivatives - Taherivardanjani, S.; Blasius, J.; Brehm, Martin; Dötzer, R.; Kirchner, B. (J. Phys. Chem. A)

Cluster Analysis in Liquids: A Novel Tool in TRAVIS - Frömbgen, T.; Blasius, J.; Alizadeh, V.; Chaumont, A.; Brehm, Martin; Kirchner, B. (J. Chem. Inf. Model.)

Return to sports after ACL injury 5 years from now: 10 things we must do - Gokeler, Alli; Grassi, Alberto; Hoogeslag, Roy; van Houten, Albert; Lehmann, Tim; Bolling, Caroline; Buckthorpe, Matthew; Norte, Grant; Benjaminse, Anne; Heuvelmans, Pieter; Di Paolo, Stefano; Tak, Igor; et al. (Journal of Experimental Orthopaedics)
Abstract Background The outcome after ACL reconstruction (ACLR) is in general disappointing with unacceptable number of athletes that do not return to pre-injury level of sports, high re-injury rates, early development of osteoarthritis and shorter careers. Athletes after ACLR have high expectation to return to sports which is in contrast with the current outcomes. The aim of this manuscript is to present an overview of factors that are needed to be incorporated and to personalize the rehabilitation process for an athlete who has undergone an ACLR. Level of evidence 4.
Keywords: Orthopedics and Sports Medicine

Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine